2015
DOI: 10.1118/1.4928474
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of kV CBCT image quality and dose reduction for volume‐of‐interest imaging using dynamic collimation

Abstract: The presented VOI technique offers improved image quality for image-guided radiotherapy while sparing the surrounding volume of unnecessary dose compared to full-field techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Parsons and Robar [28, 29] have developed an innovative iris-type dynamic collimator for ROI imaging in IGRT. At present they have utilized it for true conformal imaging, in which they only attempt to recover an accurate image of the specified volume-of-interest (VOI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parsons and Robar [28, 29] have developed an innovative iris-type dynamic collimator for ROI imaging in IGRT. At present they have utilized it for true conformal imaging, in which they only attempt to recover an accurate image of the specified volume-of-interest (VOI).…”
Section: Discussionmentioning
confidence: 99%
“…As such, it does not provide as much information of the surrounding anatomy as the dIWROI method presented here. The blades of the iris collimator described in [28] are copper with a thickness of 6.4 mm, twice the thickness we used; thus they will have a nonzero, though small (roughly 0.2%) transmission. In principle there is no reason the iris collimator cannot be used for IWROI imaging, although its relatively complicated blade structure would make edge matching as described above for the I 0 correction quite challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The CBCT projections were reconstructed using the FDK algorithm 6 within iTools (Varian Medical Systems, iLab GmbH, Baden, Switzerland). The preprocessing steps were simplified from previous VOI CBCT methods 4 to account for the truncation artifacts associated when reconstructing VOI projections. Prior to reconstruction, the VOI projection is masked using the a priori blade locations, eroded, the boundary of the VOI extrapolated and normalized.…”
Section: B Volume Of Interest Cbct Imagingmentioning
confidence: 99%
“…Volume of interest (VOI) CBCT offers improved image quality and dose reduction compared to full-field CBCT through reduction of scatter generation within the patient. [1][2][3][4] Chen et al 2 and Lai et al 3 have shown using a static copper collimator, scatter reductions of a factor of 6.6, compared to fullfield CBCT, for example. This resulted in a contrast-to-noise ratio (CNR) improvement of a factor of approximately 1.45, with dose reductions by a factor of 1.2 and 2.7 inside and outside the VOI, respectively, compared to full-field CBCT.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, C‐arm CBCT is often used for volume‐of‐interest (VOI) imaging, with limited contrast detection due to truncation artifacts. Building upon the concept of the bow‐tie filter, several beam modulators have been proposed to concentrate the exposure over the VOI while avoiding truncation artifacts . Beam modulators for VOI imaging are again invasive and costly to integrate, lacking flexibility since they only define a fixed aperture.…”
Section: Introductionmentioning
confidence: 99%